Contribution of biomechanical forces to inflammation‐induced bone resorption. (16th December 2016) - Nogueira, Andressa Vilas Boas; de Molon, Rafael Scaf; Nokhbehsaim, Marjan; Deschner, James; Cirelli, Joni Augusto
Abstract: Aim: This study aimed to evaluate the contribution of biomechanical loading to inflammation‐induced tissue destruction. Materials and Methods: A total of 144 adult Holtzman rats were randomly assigned into four experimental groups: control (C), ligature‐induced periodontal disease (P), orthodontic movement (OM), and combination group (OMP). On days 1, 3, 7, and 15, following baseline, nine animals from each experimental group were killed. Bone volume fraction (BVF) and bone mineral density (BMD) were measured using micro‐computed tomography. Expression and synthesis profile of cytokines and receptors of inflammation in gingival tissues were evaluated by PCR array assay and multiplex immunoassay. Results: At 15 days, the OMP group presented a significantly ( p < 0.05) lower BVF and BMD levels when compared to all the other groups. The OMP group presented the highest number of upregulated protein targets in comparison to the other groups. Furthermore, the gene expression and protein levels of CCL2, CCL3, IL‐1 β, IL1‐ α, IL‐18, TNF‐ α, and VEGF were significantly ( p < 0.05) higher in the OMP group when compared to the P group. Conclusions: In summary, mechanical loading modulates the inflammatory response of periodontal tissues to periodontal disease by increasing the expression of several pro‐inflammatory mediators and receptors, which leads to increased bone resorption.